Lesson Learned: Shaping Collaboration Among Tourism Stakeholders During Mount Agung Eruption - Bhaskara, Gde Indra (E-Journal of Tourism; Volume 9 Number 1 (March 2022), 2022)
The purpose of this study is to investigate the situation during the eruption of Mount Agung and the roles played by tourism stakeholders during the crisis. The findings of the study provide a more in-depth understanding of the lessons acquired by tourism stakeholders in Bali when dealing with catastrophic events, particularly natural disasters. For the purpose of this study, this research included interviews with 19 informants from a variety of tourist stakeholders, as well as those in charge of coping with natural catastrophes. According to the findings of the research, there are several lessons that can be learned from the eruption of Mount Agung, which will help tourism stakeholders be better prepared in dealing with all of the crises that may arise in the future. Keywords: natural disaster, tourism, volcanic, mount agung, stakeholder, crisis management